Pengaruh Kegunaan Manajemen Sumber Daya Manusia (MSDM) dalam Meningkatkan Kinerja Organisasi - Tambunan, Hotbona Novandi; Pandiangan, Saut Maruli Tua (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
All existing resources, including human resources, must be used to improve organizational performance. As a result, human resources are vital to any business. Human resources management is responsible for ensuring that everyone involved in the organization works together to maximize organizational performance. This research aims to evaluate the function of human resource management in improving organizational performance. This study uses a qualitative approach to analyze Miles and Huberman's interactions. Qualitative data analysis is carried out continuously and interactively, so that the data is saturated. Analysis consists of three main steps: data reduction, data delivery, and conclusion drawing. Human Resource Management can create an effective work environment and ensure the company has a high-quality and high-performing work team. It enables companies to face challenges, increase competitiveness, and achieve long-term success by considering elements such as transformational leadership, employee development, diversity management, and results-based performance management.